Abstinence from prolonged ethanol exposure affects plasma corticosterone, glucocorticoid receptor signaling and stress-related behaviors. (October 2017) - Somkuwar, Sucharita S.; Vendruscolo, Leandro F.; Fannon, McKenzie J.; Schmeichel, Brooke E.; Nguyen, Tran Bao; Guevara, Jasmin; Sidhu, Harpreet; Contet, Candice; Zorrilla, Eric P.; Mandyam, Chitra D.
Highlights: Chronic ethanol enhances peak CORT and does not alter nadir CORT. Acute withdrawal from chronic ethanol enhances irritability-like behavior. Withdrawal and abstinence from chronic ethanol alters GR signaling in the mPFC. Systemic mifepristone prevents withdrawal-induced alterations in GR signaling in the mPFC. Abstract: Alcohol dependence is linked to dysregulation of the hypothalamic-pituitary-adrenal axis. Here, we investigated effects of repeated ethanol intoxication-withdrawal cycles (using chronic intermittent ethanol vapor inhalation; CIE) and abstinence from CIE on peak and nadir plasma corticosterone (CORT) levels. Irritability- and anxiety-like behaviors as well as glucocorticoid receptors (GR) in the medial prefrontal cortex (mPFC) were assessed at various intervals (2h–28d) after cessation of CIE. Results show that peak CORT increased during CIE, transiently decreased during early abstinence (1–11d), and returned to pre-abstinence levels during protracted abstinence (17–27d). Acute withdrawal from CIE enhanced aggression- and anxiety-like behaviors. Early abstinence from CIE reduced anxiety-like behavior. mPFC-GR signaling (indexed by relative phosphorylation of GR at Ser211) was transiently decreased when measured at time points during early and protracted abstinence. Further, voluntary ethanol drinking in CIE (CIE-ED) and CIE-naïve (ED) rats, and effects of CIE-ED and ED on peak CORT levels and mPFC-GR were investigated during acute withdrawal (8 h) and protracted abstinence (28d). CIE-ED and ED increased peak CORT during drinking. CIE-ED and ED decreased expression and signaling of mPFC-GR during acute withdrawal, an effect that was reversed by systemic mifepristone treatment. CIE-ED and ED demonstrate robust reinstatement of ethanol seeking during protracted abstinence and show increases in mPFC-GR expression. Collectively, the data demonstrate that acute withdrawal from CIE produces robust alterations in GR signaling, CORT and negative affect symptoms which could facilitate excessive drinking. The findings also show that CIE-ED and ED demonstrate enhanced relapse vulnerability triggered by ethanol cues and these changes are partially mediated by altered GR expression in the mPFC. Taken together, transition to alcohol dependence could be accompanied by alterations in mPFC stress-related pathways that may increase negative emotional symptoms and increase vulnerability to relapse.